A construção dos sentidos no texto falado : o trabalho de seleção lexical - Rovani, Adriana Galina (2005)
This paper is situated in the spoken language field.Then, its object of investigation is, the spokent text, here conceived as the product of the interaction between two interloctors in a face to face situation. Other than the written text, in which most of the constitutive prosidures come extinguished, the spoken text, because of its own productivecharacterístics, marks, step by step, almost all the stages of its contituition, at least when we talk about the verbal activities.it means to say that the analysis of the spoken text allows us redo detailed the way of its enunciation. Under this perspective, joining the papers in which the main goal is describing and, consequently understanding the procedures that build the spoken text, specially focusing the procedure called lexical selection. The spoken text has as characteristic the fact that at least two interlocutors interact linguistically in a face to face situation, without previous planning and in a sequence that unfolds in the shift rotation. Therefore, the interlocutors plan the text as they are producing it. These production situations, particularly the simultaneity of what to say and how to say give the spoken text the trace of discontinuity that can be recognized through pauses, hesitations, interruptions, restarts, repetitions, paraphrases corrections and other activities that, seen as a hole, focus the evidence the constant and conscious work made for the speakers when making the text. In this process of building the text marked for the discontinuity, we detach the lexical searching to define certain denomination in the course of an enunciate in construction, the speaker often gives signals, explicitly through different procedures, that it is, here and now, in the enunciation, searching the best construction to define the meaning in construction and in this paper it is named as lexical selection. It is the main goal of this research, to identify and describe how the signals of the procedures manifest. After being organized in different categories, 9 according to different criteria, the analysis is focused mainly to the criteria of procedures in which the process of lexical selection happens through a succession of lexical elements, paradigmatically related, in a determinate place of the syntagmetic sequence of the enunciate that has been built. It is believed focus on the semantic movements that are unveiled in this lexical unfoldment , helping, then, to make the process building in the text and of the text much more clear